Implementasi Manajemen Produksi Usaha Kecil Makanan Jemblem - Totok Hendarto (Jurnal ABM Mengabdi, 2017)
Nowadays, processed foods are becoming highly demanded product. Singkong (Cassava) is a farming's most-planted commodity and a good source of carbohidrat after rice. In the paper, method used for this community service is assistance and enhancement method in term of production process in relation to effective used of facilities and infratructures. Production management implementation which start from resources selection, peeling, washing, cooking, smoothing, formatting, frying, and presenting turned out to improve the taste, appeareance, availability and overall customer satisfaction. Also, better usage of tools made production process become more effective and efficient. Lastly, result of this community service program has shown that the assistance program was able to increase 33% and 30% of total production and profit respectively.